Fairchild Turns 50 [News]. - Moore, S.K (IEEE spectrum)
Fairchild Semiconductor celebrates 50 years in the business. Fairchild itself was purchased by National Semiconductor, of Santa Clara, Calif., in 1987. Ten years later it was spun out as an independent company, focused on power-related chips and headquartered at one of Fairchild's original manufacturing sites in South Portland, Maine.